Funk, cultura e juventude carioca : um estudo no Morro da Mangueira - Batista, Rachel de Aguiar (2007)
This work aims to outline a study regarding the novel cultural manifestations, as well as their influence on the emergence of new actors in the contemporary scene. I hereby present some arguments for discussion on the importance of the culture on both social and identity formation of young people, and I specifically refer to the so-called Funk culture . The Funk rhythm is commonly associated with young people, particularly those poor and black, living in the suburbs (poor neighborhoods). This is why I make a connection between youth, poverty and Funk culture, in an attempt to point out that Funk may indeed represent the daily life of these young people. Considering the Funk as a phenomenon and a contemporary cultural manifestation active in Rio de Janeiro, my purpose is to investigate how the Funk incorporates young people in its expression. I also report the results of my field research, carried out in Morro da Mangueira, one of the most important slums (known as favelas) in Rio de Janeiro city. In this context, I highlight the increasing importance that the Funk culture and a whole set of urban groups associated with cultural manifestations have fulfilled on the expectations of young people. These individuals have produced, in the expressions associated with this universe, a specific form of sociability and new forms of social representation.